Improving Hemocompatibility of Membranes for Extracorporeal Membrane Oxygenators by Grafting Nonthrombogenic Polymer Brushes - Obstals, Fabian; Vorobii, Mariia; Riedel, Tomáš; de Los Santos Pereira, Andres; Bruns, Michael; Singh, Smriti; Rodriguez-Emmenegger, Cesar (Macromolecular bioscience, 2018)
Nonthrombogenic modifications of membranes for extracorporeal membrane oxygenators (ECMOs) are of key interest. The absence of hemocompatibility of these membranes and the need of anticoagulation of patients result in severe and potentially life-threatening complications during ECMO treatment. To address the lack of hemocompatibility of the membrane, surface modifications are developed, which act as barriers to protein adsorption on the membrane and, in this way, prevent activation of the coagulation cascade. The modifications are based on nonionic and zwitterionic polymer brushes grafted directly from poly(4-methyl-1-pentene) (TPX) membranes via single electron transfer-living radical polymerization. Notably, this work introduces the first example of well-controlled surface-initiated radical polymerization of zwitterionic brushes. The antifouling layers markedly increase the recalcification time (a proxy of initiation of coagulation) compared to bare TPX membranes. Furthermore, platelet and leukocyte adhesion is drastically decreased, rendering the ECMO membranes hemocompatible.
Keywords: nonthrombogenic; krevní proteiny; lidé; Cell Adhesion; Biocompatible Materials; polymer brushes; adsorpce; Humans; buněčná adheze; hemokoagulace; Adsorption; biokompatibilní materiály; Blood Coagulation; ECMO; Blood Proteins; hemocompatibility; oxygenátory membránové; Oxygenators, Membrane; Surface Properties; povrchové vlastnosti